2014
DOI: 10.1016/j.jpowsour.2013.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis for understanding and predicting battery degradations in real-life electric vehicle use

Abstract: This paper describes the statistical analysis of recorded data parameters of electrical battery ageing during electric vehicle use. These data permit traditional battery ageing investigation based on the evolution of the capacity fade and resistance raise. The measured variables are examined in order to explain the correlation between battery ageing and operating conditions during experiments. Such study enables us to identify the main ageing factors. Then, detailed statistical dependency explorations present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 53 publications
(56 reference statements)
0
39
0
Order By: Relevance
“…Honbo et al studied Li deposition on graphite via SEM and revealed dendritic and granular morphologies on pristine and grinded carbon, respectively. 123 Zier et al showed that it is possible to enhance the material contrast of Li deposition on graphite electrodes by reaction with OsO 4 . 119 The study of other anode materials such as Li 4 Ti 5 O 12 by SEM has so far not given precise information on the degradation mechanisms.…”
Section: 121mentioning
confidence: 99%
See 1 more Smart Citation
“…Honbo et al studied Li deposition on graphite via SEM and revealed dendritic and granular morphologies on pristine and grinded carbon, respectively. 123 Zier et al showed that it is possible to enhance the material contrast of Li deposition on graphite electrodes by reaction with OsO 4 . 119 The study of other anode materials such as Li 4 Ti 5 O 12 by SEM has so far not given precise information on the degradation mechanisms.…”
Section: 121mentioning
confidence: 99%
“…[1][2][3][4] Furthermore, the rise of renewable energy sources like wind and solar power, which are only intermittently available, demands reliable and highly flexible stationary energy storage solutions, which provide high capacities and predictable life-times. 2,5 Aging of Li-ion batteries is a general problem for manufacturers as they have to guarantee long-term reliability of their products.…”
mentioning
confidence: 99%
“…where SOC i,0 is the initial SOC; s i the nominal mileage; d i,h the trip distance at day h; DSOC i,h the SOC increment at [21], it is introduced to consider the capacity and mileage decreases of PrEV i , while it can be determined by…”
Section: Time Indicators Related Parametersmentioning
confidence: 99%
“…A study by Barre et al [9] investigated battery data, which was collected from a passenger EV following a predetermined driving cycle, to determine the causality between vehicle use and battery ageing. This study identified that capacity fade is primarily related to temperature and time, and impedance rise is primarily related to the current profile and the maximum current delivered by the battery.…”
Section: Introductionmentioning
confidence: 99%